2005
DOI: 10.1002/jsfa.2270
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress reduces the accumulation of rosmarinic acid and the total antioxidant capacity in spearmint (Mentha spicata L)

Abstract: Selected high-phenolic lines of spearmint were subjected to a constant 30 • C heat regimen for a period of 4 weeks to determine the effects of heat stress on soluble phenolics, phenols and rosmarinic acid biosynthesis and antioxidant capacity. Heat stress significantly reduced levels of total phenolic acids (71-87%) and soluble phenols (75-87%). This loss was concomitant with a loss of total antioxidant capacity of 21-60% after week 1 and up to 95% by week 4. High-performance liquid chromatography profiling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 18 publications
4
44
0
2
Order By: Relevance
“…These results are in line with previous studies [13] , which demonstrated that many phenolic acids, including rosmarinic acid and related polyphenols, significantly contribute to the antioxidant capacity of many fruits and vegetables. The present study opens the eventuality to explore the possible use of M. spicata L. (spearmint), which contains a considerable amount of rosmarinic acid, as a preventive and therapeutic approach in disorders related to oxidative stress but also as an antioxidant for agri-food storage.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in line with previous studies [13] , which demonstrated that many phenolic acids, including rosmarinic acid and related polyphenols, significantly contribute to the antioxidant capacity of many fruits and vegetables. The present study opens the eventuality to explore the possible use of M. spicata L. (spearmint), which contains a considerable amount of rosmarinic acid, as a preventive and therapeutic approach in disorders related to oxidative stress but also as an antioxidant for agri-food storage.…”
Section: Discussionsupporting
confidence: 93%
“…Previous HPLC analyses of spearmint (M. spicata) clones grown in a normal, controlled environment revealed that rosmarinic acid was the primary phenolic compound present. The rosmarinic acid content ranged from 55% to 85% of the total phenolics profile with the remainder of the phenolics was m-coumaric, p-coumaric, caffeic and ferulic acids [13] . Kivilompolo and Hyotylainen measured, using two-dimensional liquid chromatography with mass detection, an amount of 0.56% w/w (dry weight) of rosmarinic acid in spearmint leaves [27] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors have a direct impact on biochemical pathways, thus affecting the metabolism of secondary products. For example, spearmint plants enriched for RA exhibit a direct, negative correlation between the accumulation of RA and the antioxidant capacity spearmint extracts from plants grown at high temperatures [11]. Other researchers have found that cold temperatures can enhance the accumulation of RA in rosemary but is dependent on the chemotype [12].…”
Section: Introductionmentioning
confidence: 99%